PENDEKATAN PRAGMATIK NILAI PENDIDIKAN KARAKTER NOVEL DAN RELEVANSINYA SEBAGAI MATERI AJAR SASTRA - Azhari, Tiara Yuniar (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
AbstractThis research is motivated by the collapse of the value of character education that is being planted by students, especially high school students. The teenage age instability, students are easily influenced by the social environment; to avoid this they must get used to love reading, namely reading novels. Many life values can be taken from this novel, especially in the value of character education so it can motivate readers about the world of education that can be used as a model in behave. This research is a qualitative descriptive study. The object of this research is the novel Sekolah Pohon by Eko Kusumawijaya. Data were analyzed using qualitative descriptive analysis techniques with assessment and description of the data that had been obtained. The method of data collection is done by conducting literature studies. The result of this study are: (1) the value of character education in the novel Sekolah Pohon by Eko Kusumawijaya uses a pragmatic approach which includes religious values, honesty, discipline, hard work, creative, independent, curiosity, democratic, appreciate achievement, friendly/communicative, love of peace, likes to read, environmental care, social care, and responsibility; and (2) the novel Sekolah Pohon by Eko Kusumawijaya has relevance as a literary teaching material in high school in accordance with the syllabus and lesson plans.Keywords: novel, value of character education, pragmatic approach, teaching     material